2011
DOI: 10.1002/ar.21408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monochromatic Light on Melatonin Secretion and Arylalkylamine N‐Acetyltransferase mRNA Expression in the Retina and Pineal Gland of Broilers

Abstract: The goal of this study is to investigate the effects of various monochromatic lights on plasma melatonin (MT) levels and the expression of arylalkylamine N-acetyltransferase (AANAT) mRNA in the pineal gland and retina. A total of 160 newly hatched (posthatching day 1, P1) broilers, including intact, sham-operated, and pinealectomized groups were exposed to blue light (BL), green light (GL), red light (RL), and white light (WL) by light emitting diode (LED) system for short term (24 hr) or long term (2 weeks), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Exposure birds to LED-BL and stocked at 10 birds/m 2 are likely induce the secretion of pineal melatonin, which plays an important role in growth performance and the immune functions (Apeldoorn et al, 1999). The finding are disagree with results obtained by Jin et al (2011) indicated that the concentration of plasma melatonin under green light was the highest, followed by white light, and was the lowest in red light and blue light for broilers.…”
Section: -3-livability and European Production Efficiency Factor (Epef)mentioning
confidence: 80%
“…Exposure birds to LED-BL and stocked at 10 birds/m 2 are likely induce the secretion of pineal melatonin, which plays an important role in growth performance and the immune functions (Apeldoorn et al, 1999). The finding are disagree with results obtained by Jin et al (2011) indicated that the concentration of plasma melatonin under green light was the highest, followed by white light, and was the lowest in red light and blue light for broilers.…”
Section: -3-livability and European Production Efficiency Factor (Epef)mentioning
confidence: 80%
“…The effects of GL on the cecal tonsil disappeared after pinealectomy, indicating a close relationship between MEL and the different monochromatic lights. In addition, Jin et al () demonstrated that GL enhanced pinealocytes to secrete MEL in broilers. Collectively, the trends of development in the cecal tonsil under the different monochromatic lights were consistent with the alteration of MEL, suggesting that MEL plays a critical role in the GL‐induced promotion of development in the cecal tonsil.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the biosynthesis and secretion of MEL are affected by external light. For instance, green light (GL) enhances pinealocytes to secrete MEL in broilers (Jin et al, ). These studies implied that MEL might play a critical role in the monochromatic light‐induced development and immune state of the cecal tonsil in birds.…”
mentioning
confidence: 99%
“…Meanwhile, the melatonin concentration in GL was the greatest and was significantly greater than those in WL, RL and BL by 6.44-22.35% (P = 0.000-0.016); the difference was not observed between RL and WL (P = 0.175). After pinealectomy, the level of plasma GH (F (3,10) = 0.376) and melatonin (F (3,11) = 0.518) in various monochromatic lights decreased significantly, especially in GL. However, the differences disappeared among the four light treatments (P > 0.05).…”
Section: Changes In Gh and Mel Concentrations In Plasmamentioning
confidence: 99%